Membangun Biota Mini, Menanamkan Rasa Cinta Lingkungan: Program Edukasi Aquascape dan Pemeliharaan Ikan bagi Siswa di SD Negeri Kebalenan, Banyuwangi - Dinda Febta Meliyana; Sri Nurul Utami; Kharisma Orchida; Aliyati Maninda; Tubagus Sena Mulya; Trisma Cahya Amelia; Kharel Adi Putra; Arina Syarifatal Afidah (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
Technological developments and modern lifestyles have indirectly changed the way elementary school children interact with their surroundings. Most of them spend all day playing with gadgets. The lack of physical interaction with the natural environment is not just a matter of preference, but can also affect many important aspects of child development. Therefore, an innovative approach is needed to bridge this gap, namely, through aquascape training. Aquascape is the art of arranging and combining aquatic plants, water, sand, stones, driftwood, and other elements in a playful manner through a combination of underwater aesthetic styles in an aquarium. The purpose of this training is for children to be invited to directly recognize and understand aquatic ecosystems, but also to actively practice their responsibility, creativity, and awareness. Thus, it is hoped that aquascape training can divert a small portion of screen time to more meaningful real experiences, shaping a generation that is more connected to nature and the surrounding environment. The community service program was conducted for 110 fifth-grade students at Kebalenan State Elementary School in Banyuwangi Regency on January 14, 2025. The activity was carried out in person. Session 1 focused on Environmental Education and Ornamental Fish, while Session 2 involved training in creating a simple aquascape. During the training, the students showed high motivation, enthusiasm, and interest in participating in the activity.